Stable carbon isotope tree-ring records (Coppermine River, Nunavut, Canada) 1900- 2003 ... - Andreu-Hayles, Laia; Oelkers, Rose; Levesque, Mathieu (NSF Arctic Data Center, 2023)
Carbon isotope discrimination records of white spruce (Picea glauca [Moench] Voss) trees sampled along the Coppermine River (67º23’N / 115º92’W, 210 m a.s.l.) in 2004. When using this dataset, please cite: Lévesque, M., Andreu-Hayles, L., D’Arrigo, R., Oelkers, R., & Buckley, B. M. (2023). Non-linear Growth and Physiological Responses of White Spruce at North American Arctic Treeline. Journal of Geophysical Research: Biogeosciences, 128, e2022JG007096. https://doi.org/10.1029/2022JG007096 and for the methodology: Andreu-Hayles, L., Levesque, M., Martin-Benito, D., Huang, W., Harris, R., Oelkers, R., Leland, C., Martin-Fernández, J., Anchukaitis, K.J. and Helle, G. (2019). A high yield cellulose extraction system for small whole wood samples and dual measurement of carbon and oxygen stable isotopes. Chemical Geology, 504, 53-65. Project abstract: Temperatures in Arctic and subarctic North America are rising and are projected to continue to rise. Furthermore, atmospheric carbon dioxide is increasing around ...